The birth weight in pregnant women with Asherman syndrome compared to normal intrauterine cavity: A case-control study. Issue 32 (August 2018) - Baradwan, Saeed; Baradwan, Afnan; Bashir, Muhammad; Al-Jaroudi, Dania
Abstract : Abstract: Women with Asherman syndrome (AS) have damaged endometrium and reduced blood flow to the uterus and placenta which may lead to low birth weight and several obstetric complications. The objective is to determine the association between low birth weight and obstetrical complications in women with AS compared to women with normal intrauterine cavity. A retrospective case-control study was conducted in Women's Specialized Hospital, King Fahad Medical City, from December 2008 to December 2015. Pregnant women with AS undergoing hysteroscopic adhesiolysis who presented to our clinic were matched for age, parity, body mass index, methods of conception, and gestational age to pregnant women without AS based on a 1:3 ratio. The main outcome measure included birth weight and obstetrical complications. The study included 56 women with 14 cases and 42 controls. Pregnant women with AS had significantly lower birth weight (2.23 ± 0.28 kg) compared with pregnant women without AS (3.13 ± 0.383 kg) ( P  < .001 odds ratio [OR] 0.029, 95% confidence interval [CI] 0.006–0.148, P  = .001). Complications of delivery including retained placenta, placenta previa, and fetal death were significantly higher in patients with AS compared with controls 28.6% 7.1%, and 7.1% compared to 4.8%, 0%, and 0%, respectively. This was statistically significant ( P  < .001). Pregnant women with AS delivered low birth weight newborns and had more obstetrical complications as compared with pregnant women with normal cavity.